Growth volatility and trade: Market diversification vs. production specialization - Adina Ardelean; Miguel A. León-Ledesma; Laura Puzzello (University of Kent, School of Economics, 2022)
We analyze how trade affects aggregate volatility using a multi-country, multiindustry, and multi-destination framework. We decompose aggregate output growth risk into destination risk, origin risk, and idiosyncratic risk (and their covariances). We then use this framework to run counterfactuals changing the degree of destination market diversification (including home) and industry specialization. Using data on 19 industrial sectors, 34 countries, and 85 destination markets for the 1980-2011 period, we find that destination risk dominates, followed by idiosyncratic risk. From the counterfactuals, we find that the effect of increased destination market diversification is quantitatively important in reducing aggregate volatility for high volatility countries. On the other hand, reducing specialization increases volatility.
Keywords: F15; F44; F61; 330; Output Volatility; Destination Shocks; Origin Shocks; Trade Diversification; Specialization